Sensitivity Analysis of Decorative Plant Business in Kendari City (Case Study on Dahlia Ornamental Plant Business) - Gasnawati, Rabiatul Adawiah; Abdi, Abdi; Hamzah, Awaluddin (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
The purpose of this study was to determine the sensitivity of ornamental plant business in Kendari City as a case study on dahlia ornamental plant business. This research was conducted in Kendari City which was determined purposively on the dahlia ornamental plant business. The research was conducted from July to November 2019. The analysis used in this study is an analysis of efficiency and income consisting of net present value (NPV) income benefit ratio (NBCR), internal rate of return (IRR), payback period (PBP). The results of the sensitivity analysis of ornamental plant businesses with increased production costs by 5% and selling prices decreased by 5%, the value of the NPV, NBCR, IRR and payback period shows a good value so that the ornamental plant business is feasible to be cultivated because it can return all investment costs used